2009
DOI: 10.1091/mbc.e08-12-1196
|View full text |Cite
|
Sign up to set email alerts
|

Loss of E-Cadherin–mediated Cell–Cell Contacts Activates a Novel Mechanism for Up-Regulation of the Proto-Oncogene c-Jun

Abstract: Loss of E-cadherin-mediated cell-cell contacts can elicit a signaling pathway that leads to acquisition of an invasive phenotype. Here, we show that at the receiving end of this pathway is the proto-oncogene c-Jun, a member of the activator protein-1 family of transcription factors that play a key role in stimulation of cell proliferation and tumor promotion. Cell separation or abrogation of E-cadherin-mediated cell-cell contacts both cause a dramatic increase in accumulation of the c-Jun protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…Total RNA was isolated from tissue samples using the RNAeasy Mini Kit (Qiagen) and from cell cultures using the EZ-RNA reagent (Biological Industries) according to the manufacturers' instructions. RNA was analyzed by Northern blot and quantitative RT-PCR as previously described (18). The detailed protocol is included in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Total RNA was isolated from tissue samples using the RNAeasy Mini Kit (Qiagen) and from cell cultures using the EZ-RNA reagent (Biological Industries) according to the manufacturers' instructions. RNA was analyzed by Northern blot and quantitative RT-PCR as previously described (18). The detailed protocol is included in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Although expression of c-Jun is known to be mainly activated by the MAPK pathway, recent studies have shown that c-Jun expression can also be activated by a cytoskeleton-dependent pathway (18,22,23). This latter pathway does not affect the transcription of the c-Jun gene or the stability of the c-Jun protein but, rather, the translatability of its transcript (22).…”
Section: Accumulation Of C-jun Contributes To the Malignant Propertiementioning
confidence: 99%
See 2 more Smart Citations
“…More recent studies have shown that a decrease in E-cadherin expression or its translocation from the plasma membrane to the cytoplasm and/or nucleus can be crucial events in adherent junction destabilization (Gloushankova, 2008;Salahshor et al, 2008;Elston et al, 2009;Knirsh et al, 2009). In addition, it has been shown that E-cadherin is expressed in not only canine cutaneous histiocytomas, but also multiple other canine round cell tumors, including MCTs, plasma cell tumors, histiocytic sarcomas and epitheliotropic lymphomas .…”
Section: Introductionmentioning
confidence: 99%